Nonenzymatic electrochemical lactic acid sensor using CuO nanocomposite - M.S., Sajna (2023)
The detection of biochemical performance and health parameters using wearable sensors have gained more attention. Lactic acid (LA) sensor was developed using the simple facile method for electrochemical detection in artificial sweat. The non-enzymatic LA sensing characteristics were assessed using cyclic voltammetry and amperometry response with a three-electrode system. The CuO nanoparticles were applied to a glassy carbon electrode (GCE) as a single-step modification using the Nafion matrix. In order to examine the CuO material used to modify the glassy carbon electrode, various analytical methods were used such as Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible spectroscopy (UV–Visible), and X-ray powder diffraction (XRD). The minimum detectable concentration for lactic acid was found to be 0.05 × 103 mol/l. The present investigation provides an excellent pathway for the specific detection of LA biomolecule for medical purposes by a non-enzymatic approach.